2018
DOI: 10.1038/s41598-018-21954-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of strain distribution, migratory potential, and invasion history of fall armyworm populations in northern Sub-Saharan Africa

Abstract: Fall armyworm (Spodoptera frugiperda J.E. Smith) is a noctuid moth pest endemic throughout the Western Hemisphere that has recently become widespread in sub-Saharan Africa. There is a strong expectation of significant damage to African maize crop yield and a high likelihood of further dispersal, putting the rest of the Eastern Hemisphere at risk. Specimens from multiple locations in six countries spanning the northern portion of the infested region were analyzed for genetic markers. The similarity of haplotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
146
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(158 citation statements)
references
References 32 publications
10
146
1
1
Order By: Relevance
“…Pheromone differences have been reported for the strains (Groot et al, 2008;Lima & McNeil, 2009), but the lures tested to date in the Western Hemisphere show no evidence of strain differences in their attractiveness Unbehend et al, 2013). However, our studies of fall armyworm from Africa found oddities in the composition and distribution of diagnostic strain markers that bring into question whether the strain preferring rice is present in Africa or is behaving as expected with respect to host preference (Nagoshi et al, 2018). However, our studies of fall armyworm from Africa found oddities in the composition and distribution of diagnostic strain markers that bring into question whether the strain preferring rice is present in Africa or is behaving as expected with respect to host preference (Nagoshi et al, 2018).…”
Section: Introductioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Pheromone differences have been reported for the strains (Groot et al, 2008;Lima & McNeil, 2009), but the lures tested to date in the Western Hemisphere show no evidence of strain differences in their attractiveness Unbehend et al, 2013). However, our studies of fall armyworm from Africa found oddities in the composition and distribution of diagnostic strain markers that bring into question whether the strain preferring rice is present in Africa or is behaving as expected with respect to host preference (Nagoshi et al, 2018). However, our studies of fall armyworm from Africa found oddities in the composition and distribution of diagnostic strain markers that bring into question whether the strain preferring rice is present in Africa or is behaving as expected with respect to host preference (Nagoshi et al, 2018).…”
Section: Introductioncontrasting
confidence: 47%
“…Larval data from Africa were used from a previous study (Nagoshi et al, 2018). Larval data from Africa were used from a previous study (Nagoshi et al, 2018).…”
Section: Analyzing Tpi Strain Markersmentioning
confidence: 99%
“…The multiple inter-continental invasions of the fall armyworm is a serious global issue in agriculture. A marker-based study shows that these invasive populations were originated from the Florida-Caribbean region 45 . Therefore, the invasive population might carry the insecticide resistance CNVs, identified in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The FAW at least consist of two morphological identical but genetically distinct subpopulations, the corn strain (C strain) and rice strain (R strain) 33-35 . The two strains have their own preferable host plants.…”
Section: Introductionmentioning
confidence: 99%